Field programmable gate array implementation of a time domain reflectometer and ground-penetrating radar transceiver - Balon, Siegfred D. (Quezon City College of Engineering, University of the Philippines Diliman, 2011)
The thesis presents a novel approach to developing a reconfigurable transceiver capable of performing both impulse time domain reflectometry (TDR) and pulsed ground-penetrating radar (GPR) sensing functions. The transceiver is capable of arbitrary waveform generation (AWG) at the transmitter enabling generation of pulses of varying pulse shape and pulse width without recompiling and reprogramming the transceiver configuration; this will be helpful in adapting to different field operating requirements. The transceiver was prototyped using an FPGA and used a digital-to-analog converter (DAC) to realize the AWG. Limited by the DAC, the transmitter was able to achieve the narrowest pulse width equal to 6.25 ns giving a 62.5 cm range resolution. On the other hand, the receiver having an external delay generator was able to perform equivalent time sampling to attain a 0.357 ns equivalent time sampling period of 2.8 GHz sampling rate. This achieves approximately 3.6cm accuracy on the distance of a reflector from the transceiver port as tested in RG58 cables. It was shown that with minor hardware and software modifications, the system can theoretically obtain a minimum of 15.625 picoseconds equivalent time sampling period, or a maximum of 64 GHz equivalent time sampling rate, giving 1.5625 mm accuracy for TDR in RG58. The 3.6cm distance or 0.36ns time accuracy of the transceiver was verified by testing open-circuit terminated cables of varying length. The 62.5cm range resolution was likewise verified by testing cable setups with two differently-spaced discontinuities. With this positive results of the TDR experiments, it was shown that changing the medium from TDR cables to GPR antennas, the system will be feasible to perform GPR transceiver applications. However, high voltage amplification and efficient antennas are required for the GPR to work effectively. Design constraints and bottleneck were also discussed to give way for further improvements in the implementation.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Field programmable gate arrays; Ground penetrating radar; Reflectometer; Time domain reflectometry (TDR).